Decay by ectomycorrhizal fungi couples soil organic matter to nitrogen availability. (17th November 2021) - Argiroff, William A.; Zak, Donald R.; Pellitier, Peter T.; Upchurch, Rima A.; Belke, Julia P.
Abstract: Interactions between soil nitrogen (N) availability, fungal community composition, and soil organic matter (SOM) regulate soil carbon (C) dynamics in many forest ecosystems, but context dependency in these relationships has precluded general predictive theory. We found that ectomycorrhizal (ECM) fungi with peroxidases decreased with increasing inorganic N availability across a natural inorganic N gradient in northern temperate forests, whereas ligninolytic fungal saprotrophs exhibited no response. Lignin‐derived SOM and soil C were negatively correlated with ECM fungi with peroxidases and were positively correlated with inorganic N availability, suggesting decay of lignin‐derived SOM by these ECM fungi reduced soil C storage. The correlations we observed link SOM decay in temperate forests to tradeoffs in tree N nutrition and ECM composition, and we propose SOM varies along a single continuum across temperate and boreal ecosystems depending upon how tree allocation to functionally distinct ECM taxa and environmental stress covary with soil N availability. Abstract : Ectomycorrhizal fungi with peroxidases decline with increasing soil inorganic nitrogen availability. Lignin‐derived soil organic matter and total soil carbon are negatively correlated with ectomycorrhizal fungi with peroxidases, causing soil carbon storage to increase with increasing soil inorganic nitrogen. Naturally high soil inorganic nitrogen availability in temperate forests promotes soil carbon storage by reducing the decay of lignin‐derived soil organic matter by ectomycorrhizal fungi with peroxidases.